Managerial Communication Madrasah Principals In Improving Quality Of Education In Mts N 1 Kolaka - Muhammad Akbar (Journal of Research and Multidisciplinary, 2019)
Communication become an important topic in an effort to improve the quality of education in madrasah. The success communication of headmaster expected to improved the quality management of education in madrasah. At research the author was used a qualitative method, The subjects of this study was the head of the madrasah and complete of the data from teachers, students and the societies. For data collection techniques in this study used the method of observation, interviews and documentation. Communication managerial of headmaster in improving the quality of education in MTs Negeri 1 Kolaka there were divided into three kinds of communication, namely (1) Communication from top to bottom, in the form of assignment instructions, reasoning tasks and evaluating employee performance, (2) Communication from below up, in the form of feedback and improvement suggestions in madrasah, it resolved the problems was faced. (3) Horizontal communication in the form of coordination between field mediated by the headmaster, coordination with society and coordination with sesame of headmaster, coordination with the ministries of religious and other institutions